Voltammetric determination of daminozide and its degradation product N,Ndimethylhydrazine using a boron-doped diamond electrode - Usenko, Alona; Chýlková, Jaromíra; Šelešovská, Renáta; Sedlák, Miloš; Váňa, Jiří; Bartáček, Jan; Mikysek, Tomáš (My University, 2022)
The simultaneous determination of growth regulator daminozide (DMZ) and its degradation product N,Ndimethylhydrazine (DMH) via their direct electrochemical oxidation was investigated for the first time and the mechanism of DMZ oxidation has been proposed. With regard to the very positive values of the oxidation potentials of both substances, a boron doped diamond electrode (BDDE) was used as the working electrode and Britton-Robinson buffer of pH 9 was applied as the suitable supporting electrolyte. First, a differential pulse voltammetric method for DMZ determination was developed, which provided a very low detection limit (LOD = 4.56 × 10−7 mol L−1). DMH could also be determined under the same experimental conditions (LOD = 2.16 × 10−7 mol L−1). The proposed extraction technique then allowed the determination of concentrations up to 50 times lower. In case of the mixture analysis, while the determination of DMH was not affected by the presence of DMZ, the results of the DMZ analysis were significantly influenced by the presence of its degradation product. Therefore, a method for removing DMH from a sample was also developed in this work. Finally, real samples of a commercially available pesticide preparation and spiked natural and rinsing waters were successfully analyzed.
Voltametrické stanovení daminozidu a jeho degradačního produktu N,Ndimethylhydrazinu pomocí borem dopované diamantové elektrody
Keywords: growth regulator; daminozide; N,N-dimethylhydrazine; oxidation mechanism; voltammetry; boron doped diamond electrode; regulátor růstu; daminozid; N,N-dimethylhydrazin; oxidační mechanismus; voltametrie; Borem dopovaná diamantová elektroda